Penyuluhan Kegawat Daruratan pada Penyakit Kronis di Puskesmas Maccini Sawah - Magdalena Limbong; Nurbaiti Nurbaiti; Ekayanti Hafidah Ahmad; Iin Salsabila; Karsum H. Isa (Jurnal DIKMAS, 2022)
Elderly people tend to experience chronic diseases because there is a decrease in the function of organs in the body. An increase in life expectancy will correspond to an increase in the number of sufferers of chronic diseases, because every elderly person has one or more chronic diseases. It is important for seniors to understand the emergency conditions they may experience, because fluctuations in an elderly person's condition can occur in a short time. This Community Service aims to increase the elderly's understanding of emergency conditions in chronic diseases. The method used is providing health education through counseling and conducting pre-tests and post-tests to determine the understanding of the elderly. After the test was carried out, it was found that there was an increase in the value of participants' knowledge regarding the emergency conditions of chronic diseases after being given counseling with a frequency during the pretest, namely 5 people, the sufficient category was 7 and the highest was the insufficient category, namely 8 people, but after the counseling was carried out for 30 minutes, it was possible to increase knowledge. There were 16 participants who had good knowledge and only 4 people who had sufficient knowledge. With increased knowledge, it is hoped that patients will be able to provide first aid and find the right place for further assistance if a chronic disease patient experiences an emergency at home.